Disabled Trans Sex Working College Students: Results from the 2015 U.S. Trans Survey - B. Ethan Coston; Tyler Gaedecke; Kristian Robinson (Disability Studies Quarterly, 2022)
Using data from the 2015 U.S. Transgender Survey, this paper explores disabled transgender sex working college students’ experiences within sex work economies and within other paid labor force economies, experiences while in/at college, and self-reported health outcomes. Findings indicate that disabled transgender college students experience far-reaching discrimination, harassment, violence, and economic precarity while in school. At least 11% have engaged in sex work economies, and this may partly be explained by their labor force and educational experiences. The discussion highlights specific implications for and suggestions about how to improve Identity-Based services (e.g., LGBTQ Centers, Race/Ethnicity-Based Centers, Religious Centers, Student Disability Services, Financial Aid, etc.), Health-Based services (e.g., Student Health, Counseling Services, Wellness Center, etc.), and Administrative and Policy-Based services (e.g., Dean of Students, Student Conduct, Career Service, etc.) on college campuses. We conclude that our work sheds light on how all students, but particularly disabled trans sex working students, would benefit from being better economically resourced, with stronger administrative support via cross-collaborative partnerships and programming, and informed and competent service providers, who work together—and not in isolation—to provide education to the broader campus community and outreach directly for sex positive student sexual health.
Keywords: Sex Work; College; Education; Transgender Emerging Adults; Health Disparities; Student Services; Resources; Accessibility